In vitro antimicrobial activity of ten medicinal plants against clinical isolates of oral cancer cases - Kaushal Vivek; Panghal Manju; Yadav Jaya P (BMC, 2011)
Abstract Background Suppression of immune system in treated cancer patients may lead to secondary infections that obviate the need of antibiotics. In the present study, an attempt was made to understand the occurrence of secondary infections in immuno-suppressed patients along with herbal control of these infections with the following objectives to: (a) isolate the microbial species from the treated oral cancer patients along with the estimation of absolute neutrophile counts of patients (b) assess the in vitro antimicrobial activity medicinal plants against the above clinical isolates. Methods Blood and oral swab cultures were taken from 40 oral cancer patients undergoing treatment in the radiotherapy unit of Regional Cancer Institute, Pt. B.D.S. Health University, Rohtak, Haryana. Clinical isolates were identified by following general microbiological, staining and biochemical methods. The absolute neutrophile counts were done by following the standard methods. The medicinal plants selected for antimicrobial activity analysis were Asphodelus tenuifolius Cav., Asparagus racemosus Willd., Balanites aegyptiaca L., Cestrum diurnum L., Cordia dichotoma G. Forst, Eclipta alba L., Murraya koenigii (L.) Spreng. , Pedalium murex L., Ricinus communis L. and Trigonella foenum graecum L. The antimicrobial efficacy of medicinal plants was evaluated by modified Kirby-Bauer disc diffusion method. MIC and MFC were investigated by serial two fold microbroth dilution method. Results Prevalent bacterial pathogens isolated were Staphylococcus aureus (23.2%), Escherichia coli (15.62%), Staphylococcus epidermidis (12.5%), Pseudomonas aeruginosa (9.37%), Klebsiella pneumonia (7.81%), Proteus mirabilis (3.6%), Proteus vulgaris (4.2%) and the fungal pathogens were Candida albicans (14.6%), Aspergillus fumigatus (9.37%). Out of 40 cases, 35 (87.5%) were observed as neutropenic. Eight medicinal plants (A. tenuifolius, A. racemosus, B. aegyptiaca, E. alba, M. koenigii, P. murex R. communis and T. foenum graecum) showed significant antimicrobial activity (P < .05) against most of the isolates. The MIC and MFC values were ranged from 31 to 500 μg/ml. P. aeruginosa was observed highest susceptible bacteria (46.6%) on the basis of susceptible index. Conclusion It can be concluded that treated oral cancer patients were neutropenic and prone to secondary infection of microbes. The medicinal plant can prove as effective antimicrobial agent to check the secondary infections in treated cancer patients.